Measurement Precision Under Repeatability Conditions of a Batch of Sound Power Assessment for Blenders in Reverberation Room - COSTA-FELIX, Rodrigo P.B. (Archives of Acoustics, 2016)
A set of sound power assessments was performed to determine measurement precision in specified conditions by the comparison method in a reverberation room with a fixed position array of six microphones. Six blenders (or mixers) and, complementary, a reference sound source were the noise sources. Five or six sound power calculations were undertaken on each noise source, and the standard deviation (s_r) was computed as ``measurement precision under repeatability conditions’’ for each octave band from 125 Hz to 8 kHz, and in dB(A). With the results obtained, values of s_r equal 1.0 dB for 125 Hz and 250 Hz, 0.8 dB for 500 Hz to 2 kHz, and 0.5 dB for 4 kHz and 8 kHz. Those can be considered representative as sound power precision for blenders according to the measurement method used. The standard deviation of repeatability for the A-weighted sound power level equals 0.6 dB. This paper could be used for house or laboratory tests to check where their uncertainty assessment for sound power determination is similar or not to those generated at the National Metrology Institute.